PENGARUH KUALITAS PELAYANAN DAN PROMOSI PENJUALAN TERHADAP LOYALITAS KONSUMEN (STUDI PADA PRODUK BY.U DI KOTA BANDUNG) - Girda Aulia Rishyadi; Anang Muftiadi; Tetty Herawaty (JURNAL LENTERA BISNIS, 2024)
This study aims to observe the effect of service quality and sales promotion on consumer loyalty in by.U users in Bandung City. The method used in this study is quantitative descriptive. Through the distribution of questionnaires to obtain data using a Likert scale that is processed and tested. The population in this study were consumers in Bandung City who made purchases by.U so that the population is unknown. The sample was taken using non-probability sampling, namely purposive sampling. The sample size was calculated using the Lemeshow formula to obtain 100 respondents. The results of the study and hypothesis testing in this study are that service quality and sales promotion have a positive and very significant effect on consumer loyalty with a sig. 0.000. Service quality has a positive and very significant effect on consumer loyalty with a sig. 0.001. Sales promotion has a positive and significant effect on consumer loyalty with a sig. 0.020. The results of this study indicate that the R square coefficient value is 44.9%. Data processing and testing were carried out using validity and reliability tests, correlation tests, multiple linear regression, determination coefficient analysis, T tests and F tests.